The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijms23095242
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Cell Immunity in Monoclonal Gammopathy and Multiple Myeloma: From Immunopathogenesis to Novel Therapeutic Approaches

Abstract: Multiple Myeloma (MM) is a malignant growth of clonal plasma cells, typically arising from asymptomatic precursor conditions, namely monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM (SMM). Profound immunological dysfunctions and cytokine deregulation are known to characterize the evolution of the disease, allowing immune escape and proliferation of neoplastic plasma cells. In the past decades, several studies have shown that the immune system can recognize MGUS and MM clonal cells, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T-cell immunity could be important to prevent the transition from MGUS to MM. 19,20 In severe COVID-19 a massive innate and adaptive immune response (the so-called cytokine storm) is often observed. The humoral immune response against SARS-CoV-2 has been confirmed by the presence of monoclonal IgG, IgA, and IgM in the days following infection in the serum of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T-cell immunity could be important to prevent the transition from MGUS to MM. 19,20 In severe COVID-19 a massive innate and adaptive immune response (the so-called cytokine storm) is often observed. The humoral immune response against SARS-CoV-2 has been confirmed by the presence of monoclonal IgG, IgA, and IgM in the days following infection in the serum of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, SPEP in patients with MC during a period of active infection requires monitoring to ascertain whether the observed MC is temporary. Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T‐cell immunity could be important to prevent the transition from MGUS to MM 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) represents around 10% of all hematological malignancies [ 1 , 2 ] and results from the clonal proliferation of abnormal plasma cells (PCs) in the bone marrow (BM) [ 3 ]. MM occurs mainly in the elderly population (median age at diagnosis: 70 years) [ 4 ] and is characterized by anemia, myelosuppression and bone destruction, as well as clinical consequences from the paraproteinemia on kidney function and other organ systems [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a close pathophysiological relationship between hematological diseases and the immune system, and the elucidation of these molecular mechanisms will advance the diagnosis and treatment of benign and malignant hematologic, infectious, and autoimmune diseases. Contemporary studies [ 1 , 2 , 3 , 4 , 5 , 6 ] have focused on the applications of molecular immunology in hematology, providing fresh insights into the molecular immunological mechanisms involved in the diagnosis and treatment of hematologic diseases.…”
mentioning
confidence: 99%
“…Although the mechanisms through which myeloma cell clones evade the immune system are not well understood, it has been suggested that impaired T cell function may inhibit the eradication of myeloma cell clones. Lagreca et al [ 4 ] provide an excellent review, focusing on the role of T cells and the bone marrow microenvironment in the development and progression of MM. Myeloma cell clones are assumed to acquire genetic abnormalities that favor proliferation and immune escape.…”
mentioning
confidence: 99%